Diário íntimo e/ou blog:o mesmo e o diferente na cultura do ciberespaço - Oliveira, Simone de Mello de (2005)
This work is about the changes that the new technologies are providing for society, in this case, specifically, the technologies of language in relation to writing. By so doing, we problematize the relation between discourse and society in the light of discoursive practices.The blogs were analyzed in a new social and urban space, the Cyberspace, in which they are lodged. We try to understand how such blogs work in their discoursivity and how they produce linguistic, historical and ideological meaning.So, we investigated the blogs in a discoursive perspective as a new tool that confers new meaning to personal writings, renewing them in their utilization and constitution by making them publicly known, and, mainly, by making their reading possible. We defend the hypothesis that the major differing trait of a blog with regard to a personal diary, is the discoursive event of the commentary that presents itself as a regular feature of the blog. We also highlight that the difference between a personal diary and a blog is the existence of an instituted space to commentaries which enable them to be recorded. That points to the fact that what is written is read and commented. Structurally, the present work consists of two chapters: the first one is entitled "virtualities" and is subdivided in the following five parts: "from the city space to the cyberspace";"toward a collective intelligence"; "the virtual and the current"; "from personal diary to blog", and "potential drifting points". The second chapter is entitled "possibilities of updating" and it is also subdivided into five parts: "repeating, dislocating and formulating"; "constituting a blog"; "specializing the view"; "defining categories" and "net of meanings".